Pengelolaan Layanan Sistem Kehadiran Kerja Dosen Berbasis ITIL Versi 3.0 - Suryo Widiantoro; Marfuah Marfuah; Randi Randi (LPPM Universitas Putera Batam, 2023)
Quality is something that becomes a reference in assessing something. Good performance is always associated with good quality, so that good data and information management will have an impact on good performance in order to meet the desired quality. This research aims to apply the principles of the information technology service management framework based on ITIL version 3.0 into the context of managing the development of a lecturer attendance system service within the Faculty of Computers at Universal University. Through the service design domain, this research succeeded in developing recommendations for service system development in the aspects of service catalog management, capacity management, availability management, information technology service sustainability management, and information security management. Keywords: Service management; lecturer performance; ITSM; ITIL version